1998
DOI: 10.1046/j.1365-2273.1998.00149.x
|View full text |Cite
|
Sign up to set email alerts
|

Is local anaesthesia actually beneficial in flexible fibreoptic nasendoscopy?

Abstract: Although the application of a topical local anaesthetic before fibreoptic nasendoscopy is routine practice in many otolaryngological outpatients, the actual benefit to the patient of this procedure remains in doubt. Eighty-two patients were recruited in this double-blind randomized control trial which compared the patients' experiences of fibreoptic nasendoscopy with nasal preparations of Xylocaine (lidocaine), normal saline, and no spray to the nose and throat. A visual analogue scoring system was used to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 0 publications
1
64
2
Order By: Relevance
“…Topical lignocine was associated with a greater degree of postoperative throat discomfort than placebo in the study. Sore throat is in fact a known potential side-effect of topical lignocaine [4]. Frosh et al also found that the routine use of topical lignocaine spray in the nose prior to fibreoptic nasendoscopy makes the experience more painful for the patient [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Topical lignocine was associated with a greater degree of postoperative throat discomfort than placebo in the study. Sore throat is in fact a known potential side-effect of topical lignocaine [4]. Frosh et al also found that the routine use of topical lignocaine spray in the nose prior to fibreoptic nasendoscopy makes the experience more painful for the patient [4].…”
Section: Discussionmentioning
confidence: 99%
“…Sore throat is in fact a known potential side-effect of topical lignocaine [4]. Frosh et al also found that the routine use of topical lignocaine spray in the nose prior to fibreoptic nasendoscopy makes the experience more painful for the patient [4]. It is the low pH of lignocaine solutions that has been found to be responsible for post-operative sore throat [5].…”
Section: Discussionmentioning
confidence: 99%
“…10 Their study, however, used Xylocaine spray (lidocaine), which is commonly observed to cause nasal discomfort. 9 In another trial by Bonaparte et al, pain scores were significantly reduced with local anaesthetic spray in patients with an inflammatory disorder of the nasal cavity compared to those without an inflammatory condition.…”
Section: Discussionmentioning
confidence: 99%
“…At this time a decision may be made regarding the application of a topical anesthetic and/or vasoconstrictor to the nasal mucosa to make the passage of the scope more comfortable. The effectiveness of topical anesthesia for this purpose is currently unclear with some research indicating a bene fi t and others indicating that application of these solutions do not have the desired effect of making the exam more comfortable [ 7 ] and may even lead to greater discomfort for the patient [ 8 ] . Given the equivocal evidence for the use of topical anesthesia, some clinicians will limit their preparation to administration of a vasoconstrictor and lubrication of the insertion portion of the endoscope [ 9 ] .…”
Section: Equipment and Techniquementioning
confidence: 99%